Problem-Based Learning in Senior High School Physics: A Systematic Literature Review - Mazidah, Lutfiah; Sari, Nindi Putri Indah; Festiana, Ike; Falamy, Ryna Aulia (Teaching, Learning, and Development, 2026)
This study aims to analyze the implementation of the Problem-Based Learning (PBL) model in senior high school physics through a Systematic Literature Review (SLR) approach. This method identifies research trends, developed skills, applied methodologies, and the most frequently studied physics topics within PBL contexts. Data were obtained from 21 national and international scientific articles published between 2023 and 2025. The results show that the implementation of PBL in high school physics primarily focuses on improving students’ critical thinking skills, learning outcomes, and the development of digital-based modules. Moreover, most studies employ quasi-experimental and research and development (R&D) approaches with physics materials such as Newton’s Laws, sound waves, and renewable energy. Based on this SLR, it can be concluded that PBL positively impacts students’ cognitive and metacognitive abilities, enhancing engagement and technological integration in physics education.